KNOWLEDGE, ATTITUDE AND PRACTICE OF ADOLESCENTS ON BREAST SELF EXAMINATION, A STUDY DONE AMONG FIRST YEAR CERTIFICATE FEMALE STUDENTS IN ST. MICHAEL LUBAGA HOSPITAL TRAINING SCHOOL - Nassozi Maria Njogera; Clare Mukomuzibu; Nelson Kakande (Student's Journal of Health Research, 2023)
Background. Breast cancer is the most common form of cancer among women worldwide. Regular breast self-examination has been known to effectively detect breast cancer occurrence early. The study aimed at determining the knowledge, attitude, and practice of adolescents on breast self-examination among first-year Certificate female students in St Michael Lubaga Hospital Training School, Kampala district, Uganda. Methodology: A cross-sectional study was done for 30 first-year Certificate female students in St Michael Lubaga Hospital Training School, Kampala, Uganda. Data was analyzed using Excel and presented in front of tables. Results: The results of the study showed that the majority 23(76.7%) of the respondents knew about breast cancer and breast self-examination, with the majority 15(75%) having got the information from health workers. However, the majority 25(83.3%) had a fairly good attitude towards BSE and the majority of them had a fairly good practice of BSE. Conclusion: Generally, knowledge of breast cancer and breast self-examination is good among adolescents. However, their attitude towards breast self-examination is relatively average and the practice is fairly good. Recommendation: This calls for the organization of education sessions to further create awareness of breast self-examination among the adolescents in St Michael Lubaga Hospital Training School.